Efektivitas Pelatihan Ketenaganukliran Dalam Meningkatkan Kompetensi Dan Kelulusan Ujian Lisensi - Hastari, Pramaning Tri; Sinedu, Susi Susanti; Hakim, Luqman; Halizah, Nur (Balai Diklat Keagamaan Bandung, 2025)
This study aims to examine the effectiveness of nuclear training in enhancing participants’ competencies and its relationship with the licensing examination pass rate. The research involved 98 civil servants who attended various nuclear training programs conducted by DPK BRIN in 2024. A quantitative approach was employed, utilizing a paired sample t-test to assess differences between pre- and post-test scores, Spearman correlation to analyze the relationship between training improvement and remedial examinations, and binary logistic regression to evaluate the effects of age, gender, and educational background on licensing success. The results indicate a significant improvement in participants’ competencies after training and a significant negative correlation between training achievement and the frequency of remedial licensing exams. Age was found to significantly influence licensing success, while gender and educational background had no substantial effect. The study concludes that nuclear training is effective in improving competencies and facilitating licensing exam success, with practical implications for curriculum design, blended learning strategies, and human resource development policies in the nuclear sector. Keywords: nuclear training; effectiveness; competency; licensing examination